Clinical and epidemiological characteristics of salmonellosis - Adedeji, M. O.; Onishchenko, T.; Оніщенко, Тетяна Євгенівна (Запорізький державний медичний університет, 2019)
Salmonellosis is called the "disease of civilization" which widespread throughout the world. Currently trying to reduce the incidence rate by limiting the prevalence among the main sources of infection. The purpose of our work is to study the clinical and epidemiological characteristics of the gastrointestinal form of salmonellosis based on the materials ZRIH. It was surveyed 97 patients. The average age patients were (40,1 ± 2,5) years, male-62 patients, female-35. All cases are bacteriologically confirmed. S.Blegdam was isolated in 72 (74,3%) patients, S.Typhimurium in 12 (12,4%), S.Cottbus, S.Tshiogute, S.Virchov in others. In 42 (43,3%) patients, salmonella were isolated in association with Enterobacter, Klebsiella, etc. 57 (58,8%) patients associated their illness with the use of infected eggs or products that included eggs, 24 (24,7%) patient - with meat products, 9 (9,3%) - dried fish, 6 (6,2%) - cottage cheese, sour cream, bought on the market. The disease in 90 (92.7%) patients had moderate course, in 7 (7,3%) - severe. In 3 patients, dehydration shock was diagnosed. In 60 (61,8%) patients fever was observed from 38.1 °C to 40° C, in 77 (79,3%) - dehydration1-2-3st.
Keywords: тези доповідей